Proceedings of the 49th Annual ACM SIGACT Symposium on Theory of Computing 2017
DOI: 10.1145/3055399.3055412
|View full text |Cite
|
Sign up to set email alerts
|

Almost-polynomial ratio ETH-hardness of approximating densest k-subgraph

Abstract: In the Densest k-Subgraph (DkS) problem, given an undirected graph G and an integer k, the goal is to find a subgraph of G on k vertices that contains maximum number of edges. Even though Bhaskara et al.'s state-of-the-art algorithm for the problem achieves only O(n 1/4+ε ) approximation ratio, previous attempts at proving hardness of approximation, including those under average case assumptions, fail to achieve a polynomial ratio; the best ratios ruled out under any worst case assumption and any average case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 43 publications
1
104
0
Order By: Relevance
“…To the best of our knowledge, this is the only known hardness of approximation result for DALkS. We remark that DALkS is a variant of the Densest k-Subgraph (DkS) problem, which is the same as DALkS except that the desired set S must have size exactly k. DkS has been extensively studied dating back to the early 90s [10,18,20,23,[42][43][44][45][46][47][48][49][50][51][52]. Despite these considerable efforts, its approximability is still wide open.…”
Section: Densest At-least-k-subgraphmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the only known hardness of approximation result for DALkS. We remark that DALkS is a variant of the Densest k-Subgraph (DkS) problem, which is the same as DALkS except that the desired set S must have size exactly k. DkS has been extensively studied dating back to the early 90s [10,18,20,23,[42][43][44][45][46][47][48][49][50][51][52]. Despite these considerable efforts, its approximability is still wide open.…”
Section: Densest At-least-k-subgraphmentioning
confidence: 99%
“…Despite these considerable efforts, its approximability is still wide open. In particular, even though lower bounds have been shown under stronger complexity assumptions [10,18,20,23,50,52] and for LP/SDP hierarchies [49,53,54], not even constant factor NP-hardness of approximation for DkS is known. On the other hand, the best polynomial time algorithm for DkS achieves only O(n 1/4+ε )-approximation [49].…”
Section: Densest At-least-k-subgraphmentioning
confidence: 99%
“…We provide a few incomplete results related to this situation. This is NP-hard even with the restriction that M is an adjacency matrix of a graph because it then reduces to the densest k-subgraph problem, which is known to be NP-hard [21].…”
Section: Bisparsity Structurementioning
confidence: 99%
“…Although hardness of approximation of DkS within up to polynomial factor is not known, inapproximability up to almost polynomial factor is known assuming the exponential time hypothesis (ETH) and its gap version (Gap-ETH). 5 Specifically, Manurangsi [Man17] has shown that under the ETH assumption (the Gap-ETH assumption, respectively), DENSEST-k-SUBGRAPH is hard to approximate to within a factor of n 1/poly(log log n) (n o (1) , respectively). Together with Theorem 14, this implies the following corollary.…”
Section: Definition 13mentioning
confidence: 99%
“…We first show FPT inapproximability of Copeland α -SHIFT-BRIBERY with unit prices, parameterized by the number of unit shifts (Theorem 16). To do so, let us recall the following hardness result regarding distinguishing a graph with a k-clique and one in which every k-vertex subgraph is sparse, as proved by Chalermsook et al [CCK + 17] (which, in turn, relies heavily on the reduction and the main lemma of Manurangsi [Man17]).…”
Section: Parameterization By the Number Of Unit Shiftsmentioning
confidence: 99%